Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips. (1st March 2023) - Ye, Zhi-hao; Chen, Xiao-tong; Zhu, Hai-yan; Liu, Xiao-qian; Deng, Wen-hui; Song, Wei; Li, Da-xiang; Hou, Ru-yan; Cai, Hui-mei; Peng, Chuan-yi
Graphical abstract: Highlights: SERS method for AAm determination assisted with agglomeration was developed and validated. Raman characteristic peak for the detection of AAm was determined at Δv = 1449 cm −1 . Aggregating agent of 0.5 M NaCl provided the highest enhancement of SERS intensity for AAm. The LOD, recoveries and RSD were 2.5 μg/L, 94.67 %-117.50 %, and 8.43 %-12.29 %, respectively. Abstract: This study developed a simple, rapid, stable, and reliable technique for acrylamide (AAm) detection through surface-enhanced Raman scattering (SERS) on an AgNPs substrate with an aggregating agent. Specifically, the agglomeration effects of five types of salt solutions (NaCl, KCl, MgCl2, Na2 SO4, and MgSO4 ) were investigated at different concentrations and optimized using an orthogonal experiment. The optimal amounts of the aggregating agent, analytes, and AgNPs were 4, 4, and 12 μL, respectively. A linear relationship (peak area I1449 = 7.4197x + 5984.8, R 2 = 0.9971) between the characteristic peak area and AAm concentration was established in the range of 10 to 500 μg/L, and the LOD was 2.5 μg/L. The recoveries and relative standard deviations in the analysis of potato chips samples were 94.67 %–117.50 % and 8.43 %–12.29 %, respectively. The results of the proposed method were consistent with those obtained by LC-MS/MS method. This study demonstrated that SERS has excellent potential for application in the qualitative and quantitative analyses of AAm in fried foods.